2007
DOI: 10.1248/bpb.30.2113
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Dehydroxylation of Enterodiol and Enterolactone Precursors by Human Intestinal Bacteria

Abstract: Phytoestrogens are defined as plants-derived compounds with estrogen-like activities. Isoflavones and lignans have been categorized as phytoestrogens, based on their chemical structures and activities.1,2) Phytoestrogens have been explored in the field of metabolic degradation by intestinal bacteria. [3][4][5][6][7][8][9] In particular, the biotransformation of plant lignans, such as secoisolariciresinol diglucoside (SDG), pinoresinol diglucoside (PDG), arctiin, and matairesinol to mammalian lignans, enterodio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…As shown in Table 5, the reported association between lignan polyphenols and equol suggests that they are metabolized by the same pathway [25]. It has been suggested that some of the bacterium strains, for example, Eggerthella sp, were associated with both the metabolism of daidzein to equol and that of lignan polyphenols to enterodiol and enterolactone [26,27]. However, the specific intestinal bacteria and pathway responsible for metabolism of these two groups of phytoestrogens need to be identified in the future.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 5, the reported association between lignan polyphenols and equol suggests that they are metabolized by the same pathway [25]. It has been suggested that some of the bacterium strains, for example, Eggerthella sp, were associated with both the metabolism of daidzein to equol and that of lignan polyphenols to enterodiol and enterolactone [26,27]. However, the specific intestinal bacteria and pathway responsible for metabolism of these two groups of phytoestrogens need to be identified in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The latter bacterium could transform (+)-dihydroxyenterodiol (DHEND) to (+)-END, but not (−)-DHEND to (−)-END (Jin, Zhao, Nakamura, Akao, Kakiuchi, Min, et al, 2007). The aforementioned authors isolated a different bacterium, strain ARC-1, capable of dehydroxylating (−)-DHEND to (−)-END from human faeces.…”
Section: Microbiota Responsible For the Conversion Of Plant Lignans Tmentioning
confidence: 99%
“…SDG-2 and strain ARC-1 enantioselectively dehydroxylate dihydroxyenterolactone (DHENL) and dihydroxyenterodiol (DHEND). 23) Eg. sp.…”
mentioning
confidence: 99%